AN OPTION FOR SPECIAL SEPARATION OPERATIONS: MEMBRANE PROCESSES - Salt, Yavuz; Dincer, Salih (YILDIZ TECHNICAL UNIV, 2006)
Membrane processes are alternative separation technologies to the conventional separation techniques such as distillation, adsorption, absorption and extraction. The key factor in all membrane processes is the membrane which is used as the separation agent. Membranes can be made of polymer, glass, metal or liquid, and can be porous/nonporous, symmetric/asymmetric or composite. Membrane separation processes provide several advantages such as high selectivity, low energy consumption, moderate cost to performance ratio and modularity over conventional separation processes. In addition they can be coupled to conventional separation processes to form hybrid processes. In this article, an overview of membranes and important membrane processes is presented.
Keywords: Membrane; separation; Engineering